Ekspresi Pengalaman Batin Penyair dalam Puisi Aku Ingin Karya Sapardi Djoko Damono; Kajian Kritik Sastra Ekspresif - Yohana Nia Reza Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the expression of the poet’s inner experience in the poem Aku Ingin by Sapardi Djoko Damono using an expressive literary criticism approach. The research employs a descriptive qualitative method with data consisting of poetic lines and expressions in the poem. Data were collected through documentation study and analyzed interpretatively. The results show that the poet’s inner experience is implicitly expressed through simple diction, natural imagery, symbols, and concise line structures. The poem represents sincere, reflective love and an attitude of acceptance toward human limitations. This study places the poet’s inner experience as the central focus in poetic analysis.